The Impacts of Coaching on Innovative Food Business Performance: A Study of Indonesian Entrepreneurship Development Program - Suhartanto, Eko (Universitas Airlangga, 2024)
Business coaching has emerged as a prominent tool for enhancing organizational performance and individual development. Relying on the Goal-setting theory, this article uses qualitative method to provide an empirical study about the impacts of the GROW (Goals, Reality, Options, and Will) model of business coaching on product development, managerial improvement, and fulfilment of legal aspects on top of financial aspects for Indonesian micro and small food businesses. The study was conducted based on the results of the Indonesian Food Innovation (IFI) coaching program; an entrepreneurship development activity initiated by the Indonesian Ministry of Industry. The data in this study was gathered from the tracery study carried out by the IFI committee. Conducting an experiment method using comparative of pre- and post-activities, this research compares the participants’ business performance before vs. after coaching intervention, this study finds evidence of the significant positive impacts of business coaching on enhancing business performance, such as sales value and business valuation. The success of an entrepreneurship development program is determined by the insight into vital issues that are specifically often faced in a particular industry. Therefore, entrepreneurship development programs need to be customized according to the industry.